The Use of Ambulatory Blood Pressure Monitoring As Standard of Care in Pediatrics - Peterson, Caitlin G.; Miyashita, Yosuke (Frontiers in Pediatrics, 2017)
Hypertension is a significant global health problem, responsible for 7.5 million deaths each year worldwide. The prevalence of hypertension is increasing in the pediatric population likely attributed to the increase in childhood obesity. Recent work has also shown that blood pressure tends to track from childhood to adulthood including blood pressure related target organ damage. In the last 25 to 30 years, pediatric use of ambulatory blood pressure monitoring (ABPM) has been expanding mainly in the setting of initial elevated blood pressure measurement evaluation, hypertension therapy efficacy follow-up, and renal disease. However, there are many clinical areas where ABPM could potentially be used but is currently underutilized. This review summarizes the current knowledge and the uses of pediatric ABPM and explores clinical areas where it can be very useful both to detect hypertension and its longitudinal follow-up. And thus, ABPM could serve as a critical tool to potentially prevent early cardiovascular mortality and morbidity in wide variety of populations. With solid data to support ABPM’s superiority over clinic blood pressure measurements and these clinical areas for its expansion, ABPM should now be part of standard of care in blood pressure evaluation and management in pediatrics.